In-Silico Analysis of Procyanidin Type-A Extracted From Cinnamon for Diabetes Mellitus Type 2 Treatment - Anandari, Risma Nila; Minnah, Siti Khaizatul; Widadni, Vidya Utami; Safira, Dona; Fatchiyah, Fatchiyah (JSMARTech, 2021)
Type 2 diabetes mellitus (T2DM) is the most common disease in developing countries. People with type-2 diabetes are at high risk of complications leading to disability and premature death. Procyanidin compounds in cinnamon have an insulin-like activity that can regulate normal blood sugar levels. This research aimed to investigate the interaction between Î±-glucosidase and Î±-amylase with procyanidin A and their potential for diabetes treatment therapy. Data mining receptor was downloaded from RCSB PDB and ligands from PubChem. Drug likeness properties were evaluated using SwissADME, while toxicity analysis was assessed using metatox. Molecular docking between Î±-glucosidase and Î±-amylase with procyanidin A was performed using HEX 8.0.0 and was visualized by Discovery Studio. Procyanidin A showed interaction with Î±-glucosidase by non-bonds interaction, including hydrogen, hydrostatic and hydrophobic bonds, while procyanidin A and Î±-amylase formed hydrogen and hydrophobic bonds. Procyanidin A is an alternative treatment for T2DM with a variety of supportive chemical bonds. Procyanidin A has an excellent ability to inhibit activity Î±-glucosidase and Î±-amylase in the process of breaking down glucose in the intestines.